Alpinetin: A Review of Its Pharmacology and Pharmacokinetics - Zhao, Ge; Tong, Yue; Luan, Fei; Zhu, Wenjing; Zhan, Chenglin; Qin, Tiantian; An, Weixiao; Zeng, Nan (Frontiers in Pharmacology, 2022)
Flavonoids isolated from medicinal plants have been utilized as valuable health-care agents due to their virous biological applications. Alpinetin is a natural flavonoid that occurs in many widely used medicinal herbs, and has been frequently applied in Chinese patent drugs. Accumulated evidence has demonstrated that alpinetin possesses a wide spectrum of pharmacological properties, including anticancer, antiinflammatory, hepatoprotective, cardiovascular protective, lung protective, antibacterial, antivirial, and other activities through regulating multiple signaling pathways with low systemic toxicity. However, pharmacokinetic studies have demonstrated that alpinetin may have poor oral bioavailability related to its extensive glucuronidation. Currently, there lacks a systematic review on the pharmacological effects and pharmacokinetics properties of alpinetin. In this review, we aimed to highlight the mechanism of action in various diseases as well as pharmacokinetics of alpinetin to support its therapeutic potentials, and provide a valuable reference for further developments and clinical application in the pharmaceutical industry.